ANALISIS YURIDIS PENEGAKAN HUKUM TERHADAP PEREDARAN ROKOK ILEGAL TANPA CUKAI - Irwin Irwin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Circulation of illegal cigarettes without excise is a crime that deserves to be reckoned with. In the midst of rampant free trade in Indonesia, it also affects the level of circulation of illegal goods, especially illegal cigarettes without excise, this must receive special attention. This study aims to provide an explanation regarding the legal regulation of the circulation of illegal cigarettes without excise and to find out the implementation, obstacle factors and solutions for law enforcement of the circulation of illegal cigarettes without excise by Customs and Excise Officers. This type of research is field, the approach used is normative empirical, data collection techniques through interviews with informants directly and looking for online data for secondary data, the results of which are directly analyzed through qualitative methods. The results of this study indicate that the circulation of illegal cigarettes without excise can be subject to criminal sanctions and fines and with law enforcement on the circulation of illegal cigarettes without excise, it is useful to increase the coffers of State finances from the taxation sector. Law Number 11 of 1995 concerning Excise.Keywords: Circulation, Illegal Cigarettes, Customs.